Investigating the effect of oil price uncertainty on the consumer price index in Iran: a quantile regression approach based on wavelet transformation - Marzieh Esfandiari; Ali Sargolzaie; Sajjad Sargolzaei (مدلسازی اقتصادسنجی, 2023)
Investigating the effect of oil price uncertainty on the consumer price index of countries dependent on oil revenues is of great importance. Oil revenues in oil exporting countries are among the most important and influential factors in macroeconomic variables. As the risk increases due to oil price uncertainty, the government budget is affected and this leads to the consumer price index being affected. The present study examines the effect of oil price uncertainty on the consumer price index using the quantile regression econometric model based on wavelet transformation during the period from April 2011 to April 2021 in Iran. The results of the empirical model estimation showed that the relationship between oil price uncertainty and consumer price index is inverse. In other words, with the increase of uncertainty in the price of oil, the consumer price index will decrease, and this effect is greater in the final digits than in the initial digits. Also, according to the estimation results of the wavelet transformation model, the negative effect of oil price uncertainty on the consumer price index is greater in the long term than in the short term.